2022
DOI: 10.2174/1574888x16666211209155333
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Physical Exercise and the Mesenchymal Stem Cell Secretome by Modulating Neuroinflammatory Response in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a neurodegenerative, demyelinating, and chronic inflammatory disease characterized by central nervous system (CNS) lesions that lead to high levels of disability and severe physical and cognitive disturbances. Conventional therapies are not enough to control the neuroinflammatory process in MS and are not able to inhibit ongoing damage to the CNS. Thus, the secretome of mesenchymal stem cells (MSC-S) has been postulated as a potential therapy that could mitigate symptoms and disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 110 publications
1
0
0
Order By: Relevance
“…Beside exosomes, there is evidence demonstrated that MSC secretome exerted an important role in regulating target cell functions, such as senescence [37], proliferation [20], and migration [38]. Recent studies also confirmed the protective effects of MSC secretome in neural function [39,40]. In this study, we showed that miR-132-3p could improve the effects of MSC EX in protecting neuron function.…”
Section: Discussionsupporting
confidence: 54%
“…Beside exosomes, there is evidence demonstrated that MSC secretome exerted an important role in regulating target cell functions, such as senescence [37], proliferation [20], and migration [38]. Recent studies also confirmed the protective effects of MSC secretome in neural function [39,40]. In this study, we showed that miR-132-3p could improve the effects of MSC EX in protecting neuron function.…”
Section: Discussionsupporting
confidence: 54%